A light-efficient and versatile multiplexing method for snapshot spectral imaging - David Andersson; Yupan Bao; Vassily Kornienko; Dean Popović; Elias Kristensson (Scientific Reports)
Abstract The study of rapid and stochastic events that involve multiple species, such as chemical reactions and plasma dynamics, requires means to capture multispectral information in two dimensions at both high temporal- and spatial resolution. Commercially available cameras that provide high temporal resolution are based on either signal intensification or rapid data acquisition. Intensified cameras provide extremely short acquisition times using intensification by means of micro channel plates, but the conversion between electrons and photons makes these cameras inherently monochrome. In contrast, high-speed cameras can achieve color-sensitivity through integrated Bayer filters but suffer from a reduced light collection efficiency and a fixed spectral composition. In this article we present a non-integrated optical arrangement for instantaneous multispectral imaging based on FRAME image multiplexing. By spectrally separating the signal using lossless dichroic mirrors, a 16-fold increase in light-collection efficiency is gained (compared to past solutions), resulting in an equivalent increase in temporal resolution. This improvement provides new avenues for multispectral imaging of rapid events. We demonstrate the system’s versatility and suitability for studies of such processes by applying it for (i) temperature mapping using a high-resolution CCD camera, (ii) high-speed videography up to 10 kHz at four spectral channels and (iii) dual-species visualization in a plasma discharge using an intensified sCMOS camera.